2018
DOI: 10.12688/wellcomeopenres.14867.1
|View full text |Cite
|
Sign up to set email alerts
|

Tissue and host species-specific transcriptional changes in models of experimental visceral leishmaniasis

Abstract: Background: Human visceral leishmaniasis, caused by infection with Leishmania donovani or L. infantum, is a potentially fatal disease affecting 50,000-90,000 people yearly in 75 disease endemic countries, with more than 20,000 deaths reported. Experimental models of infection play a major role in understanding parasite biology, host-pathogen interaction, disease pathogenesis, and parasite transmission. In addition, they have an essential role in the identification and pre-clinical evaluation of new drugs and v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 80 publications
(56 reference statements)
3
26
1
Order By: Relevance
“…Blood transcriptomics conducted in asymptomatic infected individuals with L. infantum as well as in active VL patients, also revealed enhancement of type I interferon pathway in both cases. The above research group suggested that the response induced by IFN-α/β signaling might have a dual role on the context and clinical status induced by L. infantum (37). Specifically, a fine regulation of IFN-α/β expression and of the transcriptional programs induced by those cytokines could promote a protective response in asymptomatic individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Blood transcriptomics conducted in asymptomatic infected individuals with L. infantum as well as in active VL patients, also revealed enhancement of type I interferon pathway in both cases. The above research group suggested that the response induced by IFN-α/β signaling might have a dual role on the context and clinical status induced by L. infantum (37). Specifically, a fine regulation of IFN-α/β expression and of the transcriptional programs induced by those cytokines could promote a protective response in asymptomatic individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Given the many studies that have identified the importance of regulatory IL-10 in VL pathogenesis [42, 47-50], it was of some interest in our study that IL10 was not identified as a top differentially expressed gene or as a significantly enriched signalling pathway in either comparison of active cases with healthy controls, or of active cases with treated cases. Nor did we observed perturbation of IL10R as has been reported in experimental transcriptional profiling studies of VL [46]. Indeed, downregulated expression of the type 2 cytokine gene IL4 was the strongest response associated with effective cure in liposome-encapsulated amphotericin B treated cases, in line with previous studies showing that IL-4 levels were two-fold higher in VL patients who had failed treatment compared to previously untreated patients, whereas IL-10 levels were comparable in both [49].…”
Section: Discussionmentioning
confidence: 61%
“…CXCL10 and CXCL9 were also identified as the most highly “induced” genes in comparing lesion transcript profiles with normal skin of patients with American cutaneous leishmaniasis, consistent with their roles in inflammatory cell recruitment [45]. Cxcl9, Gbp1 (encoding the interferon-γ-induced guanylate binding protein GBP1 identified here as one of the top 10 induced genes when comparing active versus treated cases), and Ifng were also identified as part of a common signature of 26 genes upregulated in blood, spleen and liver throughout the course of experimental infection with L. donovani in susceptible BALB/c mice, with Cxcl9 and Gbp1 reported as hub genes from a STRING analysis [46].…”
Section: Discussionmentioning
confidence: 99%
“…This gene encodes the interferon-g-induced guanylate binding protein GBP1. Of interest, three genes identified in our study, CXCL9, IFNG, and GBP1, were also identified as part of a signature of 26 genes found to be upregulated in blood, spleen and liver across the course of experimental VL in mice (Ashwin et al, 2018) and may thus be strong biomarkers that could contribute to a signature for VL disease in humans. In this murine study, Cxcl9 and Gbp1 were also reported as hub genes from a STRING analysis (Ashwin et al, 2018).…”
Section: A B Cmentioning
confidence: 73%
“…In recent years omics-based approaches have been harnessed to gain a more global picture of the interaction between host and pathogen, including in leishmaniasis [e.g. (Novais et al, 2015;Kong et al, 2017;Ashwin et al, 2018)]. Here we review results from studies using three different omics-based approaches to study VL caused by L. donovani in India: (i) chip-based analysis of single nucleotide variants used to carry out the first genomewide association study (GWAS) of VL to identify host genetic risk factors (Fakiola et al, 2013); (ii) chip-based transcriptional profiling used to compare active with cured cases (Fakiola et al, 2019), including the influence of anti-IL-10 on whole blood responses to soluble leishmania antigen (SLA) (Singh et al, 2020); and (iii) a meta-taxonomic approach based on sequencing amplicons derived from regions of 16S ribosomal RNA (16S rRNA) and 18S rRNA genes that allowed us to determine composition of both prokaryotic and eukaryotic gut microflora in VL cases compared to endemic controls (Lappan et al, 2019).…”
Section: Introductionmentioning
confidence: 99%